Social reality - Collin, Finn. (London ; New York : Routledge, 1997)
The nature of social reality is a key problem in the philosophy of social science. This book outlines the major issues - historical and contemporary - raised by social reality and social facts. What, after all, are we talking about when we talk about social reality and the facts of social life?
Social constructivism has become a very influential position, and Finn Collin reviews a number of traditional doctrines in philosophy and social science which support the constructivist position, whilst also exposing the excesses of that particular view.
This book has something to offer both philosophers and social scientists. To the former it shows how the well-worn topic of realism versus anti-realism (in the broadest sense) assumes new and interestingly varied forms when social reality is substituted for physical reality. For the social scientist, the book offers conceptual clarification of certain key issues in recent social science which are really philosophical issues.
Social Reality is written for students of philosophy and the social sciences, and lucidly explains - in terms accessible to both disciplines - the problem of social facts and social reality.
Includes bibliographical references and index.
Keywords: Reality; Constructivism (Philosophy); Ontology; Philosophy and social sciences